Identification of the Application Green Construction Concept using the Assessment Green Construction Model (MAGC) - Rahmat, Rahmat; Zola, Prima; Rifwan, Fitra (CIVED, 2024)
Environmental damage is a topic of global discussion, so there is a need to reduce the impact of this environmental damage in various sectors, including the construction sector. In the construction industry, one of the efforts is the need to implement green construction. Green construction is one part of sustainable development that is expected to be able to participate in maintaining environmental sustainability and harmony in its implementation. Until now, the application of the green construction method in sumatra has been considered to be relatively immature. This research aims to identify the application of the green construction concept using the green construction assessment model. This research is quantitative research. The data are collected through questionnaires. The assessment instrument uses the green construction assessment model (MAGC) which is combined with the analytical hierarchy process process (AHP) method for calculating aspect weights and green construction factors. This research uses six aspects, 16 factors, and 55 green assessment indicators. construction that is obtained through the green construction assessment model. Based on the results of the analysis and data processing through the Ms.Excel software, we obtained an aspect weighting result of 0.134 and a factor weight of 0.209. This value is used as a calculation for the green construction assessment model, which is obtained by a green construction value (NGC) of i3.15 which does not yet meet the ideal NGC value of 10.10.